1986
DOI: 10.3171/jns.1986.65.3.0296
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up results of selective VIM-thalamotomy

Abstract: The authors report the results of a long-term follow-up study of the effects of the physiologically defined selective VIM (nucleus ventralis intermedius)-thalamotomy on tremor of Parkinson's disease in 27 patients and essential tremor in 16 patients. The follow-up period ranged from 3.25 to 10 years (mean 6.58 years). In 43 patients a total of 50 operations (including four bilateral operations and three reoperations) were carried out. The early (2 to 4 weeks after surgery) and late effects on the tremors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0
5

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(117 citation statements)
references
References 20 publications
4
104
0
5
Order By: Relevance
“…The surgical complications (Table 2) in this group of patients were similar to those described in the literature 5,6,8,11,12,[31][32][33][34][35] . For TVL, the studies reported complication rates between 36 and 61%, for PVP they range from 6,3 to 66,6%.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The surgical complications (Table 2) in this group of patients were similar to those described in the literature 5,6,8,11,12,[31][32][33][34][35] . For TVL, the studies reported complication rates between 36 and 61%, for PVP they range from 6,3 to 66,6%.…”
Section: Discussionsupporting
confidence: 72%
“…The reports of the pre-levodopa era [2][3][4] used nonvalidated methods of assessment, and those patients presented a different clinical profile when compared to the patients of the levodopa era. More recent studies [5][6][7][8][9][10][11][12][13][14][15][16] present different methods of assessment, leading to different conclusions.…”
mentioning
confidence: 99%
“…A escolha do alvo cirúrgico neste estudo segue a tendência atual da literatura, que indica a PPV nos casos nos quais a bradicinesia, flutuações decorrentes do uso da levodopa e ocorrência de discinesias são predominantes [2][3][4]12,[14][15][16][17][18][19] . A TVL é indicada nos casos onde há predomínio da rigidez e do tremor [20][21][22][23][24] . Nosso estudo assemelha-se muito com o de Ferraz et al 25 , quanto à técnica cirúrgica e escolha do alvo cirúrgico.…”
Section: Discussionunclassified
“…Perry e Lenz 24 apresentam uma revisão de trabalhos realizados com pacientes submetidos a TVL que apresentavam complicações transitórias, dentre elas: disartria, disfasia, hemiparesia e alterações mentais. Outro trabalho também apresenta resultado semelhante 21 .…”
Section: Discussionunclassified
“…Some patients with SCA show a vigorous action tremor intractable to medical therapy. There is a long history of functional neurosurgery targeting the ventral intermediate nucleus (Vim) of the thalamus for treatment of tremor, most often for essential tremor (ET) 3, 4. ET is not associated with overt ataxia, but a subset of ET was disclosed to involve a pathological abnormality of the cerebellum .5 The mode of tremor is similar, dominantly intention‐type action tremor, and the mechanism of tremor is estimated to share the same anatomical structures in SCA and ET 5, 6.…”
Section: Introductionmentioning
confidence: 99%